Microbiomes of the Enteropneust, Saccoglossus bromophenolosus, and Associated Marine Intertidal Sediments of Cod Cove, Maine - King, Gary M. (Frontiers in Microbiology, 2018)
Enteropneusts are widely distributed marine invertebrates that accumulate high concentrations of halogenated aromatics. Some of these compounds affect benthic biogeochemistery (e.g., denitrification and ammonia oxidation), but little is known about interactions between enteropneusts and their associated microbial communities. Even less is known about enteropneust host-microbe relationships in the digestive tract. More generally, microbial community composition and diversity in intertidal sediments have received little attention. In this study, high throughput sequence analyses of 16S rRNA genes extracted from microbial communities associated with sediment-free whole individuals of Saccoglossus bromophenolosus and freshly excreted S. bromophenolosus gut sediments revealed a potential Spirochaete symbiont that was abundant, present in gut sediment, but absent in other sediments. Relative to surface sediments, gut communities also revealed evidence for selective losses of some groups and blooms of others, especially Colwellia, Photobacterium, Pseudoalteromonas, and Vibrio. After deposition, gut sediment communities rapidly resembled those of surface sediments. Although hierarchical cluster analysis and Linear Discriminant Analysis Effect Size (LEfSe) differentiated among burrow walls of S. bromophenolosus and a polychaete, Alitta virens, as well as between surface and sub-surface sediments, most operational taxonomic units (OTUs) were shared, with differences largely occurring in relative abundances. This suggests that sediment mixing through bioturbation might act to homogenize community composition, while species-specific impacts by infauna might alter local population abundances. Although Cod Cove is a relatively isolated intertidal system, microbial community members included groups with cosmopolitan distributions and roles in sulfur cycling, e.g., Gammaproteobacteria BD7 and Sva0071, as well as novel OTUs representing a large number of phyla.